The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11116-020-10110-2
|View full text |Cite
|
Sign up to set email alerts
|

What are the determinants of the willingness to share rides in pooled on-demand services?

Abstract: Simulation studies suggest that pooled on-demand services (also referred to as Demand Responsive Transport, ridesharing, shared ride-hailing or shared ridesourcing services) have the potential to bring large benefits to urban areas while inducing limited time losses for their users. However, in reality, the large majority of users request individual rides (and not pooled rides) in existing on-demand services, leading to increases in motorised vehicle miles travelled. In this study, we investigate to what exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 54 publications
6
26
0
Order By: Relevance
“…They found that the willingness to share rides is at first a time-cost tradeoff. Alonso-Gonza´lez et al (12) examined the value of time and reliability for urban pooled ondemand service. With an experimental approach, they found that the value of time for pooled on-demand services ranged from 7.88 to 10.80 euros per hour.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the willingness to share rides is at first a time-cost tradeoff. Alonso-Gonza´lez et al (12) examined the value of time and reliability for urban pooled ondemand service. With an experimental approach, they found that the value of time for pooled on-demand services ranged from 7.88 to 10.80 euros per hour.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…In the case of a high utilization of ridepooling vehicles, the reduction of the number of vehicles on the road as well as the distances covered are particularly higher, compared with other new mobility services. Theoretically, ridepooling offers economic, environmental, and societal benefits (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…These two aspects are the first to be evolved to accommodate changing needs and would feed back to the applicability and reliability of new transit options. The reflexive part is ongoing and has been reported in our earlier studies from both the perspective of the users (demand side) and the governance of FPTs ( Ali, 2017 ; Alonso-González, Liu, Cats, van Oort, & Hoogendoorn, 2018 ; Sharmeen & Meurs, 2019 ). The tactical aspects, although come across somewhat indirectly, needs more thought and knowledge of the FPT systems to be developed and communicated, as came across from the interviews conducted so far.…”
Section: Scope and Methodologymentioning
confidence: 83%
“…The authors disentangled the sharing aspect of time-cost trade off, i.e., to what extent individuals are willing to detour in order to get a discounted fare. They found the willingness to share rides primarily depended on the time-cost trade-offs [29]. In another study conducted in Ghana, it was found that young people of that region were more inclined to use a rideshare service due its convenience and cost advantages over conventional taxis [30].…”
Section: Major Research Questionsmentioning
confidence: 99%